Singing Styles - Jane Beethoven; Rosanne Emery; Cliff Lenz.; Silver Burdett Ginn. ([Columbus, OH] Silver Burdett Ginn, 1991)
Viewers see and hear many different styles of singing - -Enjoy various styles of singing, including jazz, barbershop, country, and gospel - - Hear renowned folk, pop, and country stars - -Discover differences between trained and untrained voices.
To the Teacher - - Using the Video Library - - Tips on Handling the Tapes - - For Discussion - - Correlations with THE MUSIC CONNECTION - - Student Follow-up - - Vocabulary - Music Contents - - About the Library.
Series producers : Jane Beethoven; Rosanne Emery.
Keywords: Singing; Films for the hearing impaired